51.6k views
0 votes
A=3b+c. solving for b.

User Amanpreet
by
5.2k points

2 Answers

4 votes
b=a/3- c/3

Step 1: Flip the equation.

3b+c=a

Step 2: Add -c to both sides.

3b + c + (-c)=a + (-c)

3b=a - c

Step 3: Divide both sides by 3.

3b/3= a - c/3

b=1/3a + -1/3c
User Majenko
by
5.6k points
3 votes

Answer:

a/3 -c =b

Explanation:

a=3b+c divide 3 on both sides

a/3 =b+c subtract c on both sides

a/3-c = b

I used to overthink this all the time its easy i promise :)

User Binwiederhier
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.